Pengaruh Tingkat Pengangguran dan Tingkat Kemiskinan Terhadap Indeks Pembangunan Manusia di Provinsi Aceh Periode 2010-2021 - Yuliana Yuliana; Dea Ananda; Yulfrita Adamy; Darnelly Darnelly; Azlim Azlim (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
The Human Development Index (HDI) measures human development achievements based on a number of basic components of quality of life. This study aims to determine the unemployment rate and poverty rate affect the human development index in Aceh Province. The data technique uses panel data from districts/cities of Aceh Province from 2010-2021. Data analysis using the Fixed Effect Model panel data method. The results showed that the open unemployment rate and poverty rate had a negative and significant influence on the human development index in the districts / cities of Aceh Province 2010-2021. The R² value in the study valued at 0.8930 means that the independent variable affects the dependent variable by 89.30%, the remaining 10.70% is influenced by other variables outside the model.